Progressive myoclonic ataxia and JC virus encephalitis in an AIDS patient. Issue 5 (1st May 2002) - Fontoura, P; Vale, J; Lima, C; Scaravilli, F; Guimarães, J
Abstract : A case of progressive myoclonic ataxia in an AIDS patient is described, which evolved over a 13 month period. The ataxia persisted as the only clinical finding for several months before the appearance of a severe tetraparesis and cachexia. Throughout the clinical progression, magnetic resonance imaging (MRI) revealed the presence of bilateral, progressive, isolated, and symmetrical lesions involving the red nuclei, subthalami, thalami, lenticular nuclei, and primary motor cortices. Neuropathological examination, supplemented by in situ hybridisation for JC virus DNA, confirmed that the lesions were those of progressive multifocal leucoencephalopathy (PML). The exceptional clinical presentation of PML in this case is the first report of progressive myoclonic ataxia caused by PML. The selective nature of the lesions confirms the role of the dentato-rubral-thalamo-cortical tract in the pathogenesis of progressive myoclonic ataxia. The atypical MRI findings further emphasise the need for expanded diagnostic criteria for PML in AIDS patients and support the use of more aggressive diagnostic methods as new treatments become available.